Integrasi Nilai-Nilai Islam dalam Pembelajaran Pendidikan Kewarganegaraan: Systematical Literature Review - Ali Miftakhu Rosyad; Khoiriyah, Affy (Fakultas Agama Islam Universitas Wiralodra, 2025)
The integration of Islamic values in Civic Education has become crucial for character building in Indonesia's multicultural society. This systematic literature review analyzed 45 peer-reviewed articles published between 2018-2024 to examine how Islamic values are integrated into Civic Education learning to form citizens with noble character. Using PRISMA guidelines, articles were selected from multiple databases including Google Scholar, DOAJ, and national journals. The analysis revealed four main themes: conceptual frameworks showing compatibility between Islamic values and Pancasila principles, diverse implementation strategies including curriculum design and innovative teaching methods, significant challenges in teacher competency and policy support, and positive impacts on students' spiritual awareness, tolerance, and national commitment. The study found that effective integration requires holistic approaches combining spiritual, moral, and citizenship dimensions while maintaining Indonesia's pluralistic values. This research contributes to the theoretical understanding of value integration in civic education and provides practical recommendations for educators, policymakers, and researchers. The findings suggest that when properly implemented, Islamic values integration significantly enhances character formation without compromising religious diversity and democratic principles.